Involvement of the Central Nervous System in the Salivary Secretion Induced by Pilocarpine in Rats - Renzi, Antonio [UNESP]; Colombari, Eduardo [UNESP]; Mattos Filho, T. R.; Silveira, J. E. N. [UNESP]; Saad, W. A. [UNESP]; Camargo, L. A. A. [UNESP]; Deluca, L. A. [UNESP]; Derobio, J. G. [UNESP]; Menani, José Vanderlei [UNESP] (American Association for Dental Research (AADR), 1993)
The effect in rats of an anteroventral third ventricle (AV3V) electrolytic lesion on salivary secretion induced by intraperitoneal (i.p.) or intracerebroventricular (i.c.v.) injection of a cholinergic agonist (pilocarpine) was investigated. Sham- or AV3V-lesioned rats anesthetized with urethane and with a stainless steel cannula implanted into the lateral ventricle (LV) were used. The amount of salivary secretion was studied over a seven-minute period after i.c.v. or i.p. injection of pilocarpine. In sham-operated rats, i.p. injection of pilocarpine (1 mg/kg b.w.) (after 6 h, 2, 7, and 15 days) produced salivary secretion (486 +/- 21, 778 +/- 85, 630 +/- 50, and 560 +/- 55 mg/7 min, respectively). This effect was reduced 6 h, 2, and 7 days after an AV3V lesion (142 +/- 22, 113 +/- 32, and 290 +/- 62 mg/7 min, respectively), but not 15 days after an AV3V lesion (516 +/- 19 mg/7 min). I.c.v. injection of pilocarpine (120 mug in 1 muL), in sham-operated rats after 6 h, 2, 7, and 15 days also produced salivary secretion (443 +/- 20, 417 +/- 81, 496 +/- 14, and 427 +/- 47 mg/7 min, respectively). The effects of i.c.v. pilocarpine were also reduced 6 h, 2, and 7 days after an AV3V lesion (143 +/- 19, 273 +/- 14, and 322 +/- 17 mg/7 min, respectively), but not after 15 days (450 +/- 28 mg/7 min). The results demonstrate that the central nervous system, and particularly the AV3V region, is important for the effect of pilocarpine on salivary secretion in rats. Moreover, they suggest that activation of central pathways may play an important part in the salivary secretion to peripheral pilocarpine in rats.